Coastal protection (PVD work) / Muhamad Hisyam Ikmal Mohd Rasul - Mohd Rasul, Muhamad Hisyam Ikmal (Universiti Teknologi MARA, Perak, 2022)
This report in general is about the work for coastal protection in the island to make rock bund. The coastal protection is about measures to safeguard the shore against erosion and coastline retreat, as well as coastal settlement damage and hinterland floods. Hard constructions like revetments and groins are commonly utilized in practise, while soft treatments like coastal nourishment are becoming more prevalent. Hard protection structures change erosion and sedimentation patterns along the coast, which can lead to the loss of natural coastal protection structures like beaches and marshes (so-called coastal squeeze). Also see the article Natural Barriers to Protecting the Shore. To do this coastal protection, they are use PVD work to make this rock bund. This methodology is the way that are use for the process to make the rock bund. This PVD work will short the time to make this rock bund compare to the previous way which take a long time to finish this rock bund. If use this method it will shorten the time.